A Feasibility Study for Implementation “Health Arcade”: A Study Protocol for Prototype of Multidomain Intervention Based on Gamification Technologies in Acutely Hospitalized Older Patients - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The aim of this article is to present the research protocol for a study that will evaluate the feasibility of implementation of Health Arcade prototype multidomain intervention based on physical and cognitive training using gamification technologies at improving care for older people hospitalized with an acute illness. A total of 40 older people will be recruited in a tertiary public hospital at Pamplona, Spain. The intervention duration will be four to nine consecutive days. Additionally, the patients will receive encouragement for maintaining active during hospital stay and for reducing sedentary time. Primary implementation-related outcomes will be the adherence to treatment (i.e., number of games and days completed during the intervention period), reaction or response time, and number of success and failures in each game per day. Secondary implementation-related outcomes will be self-perceived grade of difficulty, satisfaction, enjoyment per game and session, and self-perceived difficulties in handling the prototype hardware. Other health-related outcomes will also be assessed such as functional capacity in activities of daily living, mood status, quality of life, handgrip strength, physical activity levels, and mobility. The current study will provide additional evidence to support the implementation of multidomain interventions designed to target older persons with an acute illness based on friendly technology. The proposed intervention will increase accessibility of in-clinical geriatrics services, improve function, promote recovery of the health, and reduce economic costs. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.